Teachers’ Professional Development Training for Their Professionalism - Shrestha, Mina; Acharya, Bed Raj (Journal of Mathematics Education, 2023)
The Teacher Professional Development (TPD) program is a dynamic initiative dedicated to nurturing the professional growth of educators, ultimately enhancing their efficiency. This article focuses on the study and analysis of the implementation status of TPD programs in Nepal in comparison to the policy guidelines of the TPD framework 2015 and aims to improve the implementation of TPD programs for the utilization of resources. The main strength lies in investing in teachers’ training that will ultimately lead to improved teaching and learning conditions in Nepali classrooms. Although the results show that the program is well adapted for the professional development of Nepali teachers, there are many gaps in the various stages of program implementation, which could make the TPD program more effective in transferring training to the classroom. It doesn’t seem to be effective in translating the TPD policies into practices. This study also paved the way for further research to improve the transfer of training to classroom practices.